Analysis of therapeutic effectiveness and adverse effects of long-term corticosteroids among leprosy patients with reactions: A retrospective cohort study. (April 2022) - Siagian, Joyce Novelyn; Purwantyastuti,; Instiaty,; Menaldi, Sri Linuwih
Objectives: Main therapy for leprosy reactions is 12 weeks corticosteroids according to World Health Organization recommendations, but recovery cannot be achieved and recurrence occurs. Long duration of administration was thought to provide better clinical improvement. Evidence of the efficacy of corticosteroids in leprosy reactions is still lacking, and optimal dose and duration of therapy vary, while the need for long-term high-dose corticosteroids makes it difficult to avoid adverse effects. Methods: This is a retrospective cohort study analyzing the difference between therapeutic effectiveness and adverse effects of 12 weeks and >12 weeks corticosteroids, involving all new leprosy patients without age restriction, at Cipto Mangunkusumo Hospital and Cakung Community Health Center in Indonesia during 1 January 2015–31 December 2017. Secondary data were collected from medical records, and observations carried out until December 2018. Therapeutic effectiveness was assessed from clinical improvement to corticosteroids discontinuation, without 3 months recurrence after first cycle was completed. Adverse effects were assessed by all corticosteroids-related side effects. Results: Of 195 patients, 57 (29.2%) used 12 weeks corticosteroids, and 138 (70.8%) for >12 weeks. Effectiveness occurred in 38 (66.7%) of 12 weeks group and 106 (76.8%) of >12 weeks group (relative risk = 0.604, 95% confidence interval = 0.307–1.189, p = 0.143). Of 145 patients, adverse effects occurred in 12 (31.6%) of 12 weeks group and 70 (65.4%) of >12 weeks group (relative risk = 0.244, 95% confidence interval = 0.111–0.538, p < 0.001). Of 171 adverse effects, 37.4% were mild such as dyspepsia, skin disorders, and lipodystrophy, while 62.6% were severe in the form of neuropsychiatric disorders, eye disorders, cardiovascular disease, gastrointestinal bleeding, metabolic-hormonal abnormalities, and reactivation of infections. Conclusion: There is no effectiveness difference in the form of clinical improvement without 3 months recurrence, between 12 weeks and >12 weeks corticosteroid, while longer administration causes 4 times more events.